Perspectives on Developing Small Molecule Inhibitors Targeting HIV-1 Integrase - J. Tan, J.; Liu, C.; H. Sun, X.; J. Cong, X.; M. Hu, L.; X. Wang, C.; J. Liang, X. (Mini Reviews in Medicinal Chemistry, 2012)
HIV-1 integrase (IN) is a crucial enzyme in the life cycle of HIV-1 and also a validated target for developing anti-HIV inhibitors. Recent progress in drug design has significantly accelerated the development of anti-AIDS IN inhibitors. A large amount of novel inhibitors that interact specifically with IN were developed along with the expanding and application of methods to drug design. This article reviewed the anti-HIV IN inhibitors discovered by the rational drug design approaches in the recent 5-year.
Keywords: ligand-based drug design